ALGINATE-SEED ENCAPSULATION CONTAINING ENDOPHYTIC Bacillus cereus BTH21 FOR BIOCONTROLLING WILT DISEASE IN EGGPLANT - Arika Purnawati; Endang Triwahyu Prasetyawati; Haidar Fari Aditya; Saefur Rohman (BIOTROPIA, 2025)
HIGHLIGHTSSeed encapsulation using alginate and B. cereus BTH21 for biocontrol of wilt disease in eggplant.ABSTRACTBacterial wilt is a major plant disease caused by Ralstonia solanacearum that infects important crops, such as eggplant, causing wilt, stunted growth, and reduced yield. The biocontrol of the pathogen can be done by employing antagonistic bacteria, yet direct inoculation into the soils are often ineffective due to low population of the pathogen in the soils, which also easily washed away by watering activity. Seed encapsulation technique, using alginate, zeolite and peat, containing antagonistic bacteria Bacillus cereus BTH21 to control R. solanacearum is the novelty proposed in this research. Hence, this research aimed to develop alginate seed-encapsulation technique containing Bacillus cells as a mean to biologically control R. solanacearum in eggplant. Endophytic Bacillus cereus BTH21 strains was isolated from healthy eggplant tissue obtained from Kediri, East Java Province, Indonesia. Subsequent isolation, purification and molecular identification confirmed the identity of the strain. Three seed-encapsulation formulations were made: a) control (no encapsulation); b) alginate + zeolite + Bacillus (Al+Z+B); and c) alginate + peat + Bacillus (Al+P+B). A field experiment was designed in a Completely Randomized Design (CRD) where the alginate-encapsulated eggplant seeds were sown along with deliberate R. solanacearum inoculation (107 cfu/mL) into the soils. Observations were carried out every 7 days from 0 – 49 days after sowing (DAS) on several parameters, i.e., incubation period, infection rate, germination percentage, plant height, and number of leaves. The data were analyzed by using analysis of variance (ANOVA) followed by Duncan’s multiple range test at a significance level of P < 0.05. The results showed that both seed encapsulation formulations prolonged incubation period (15 and 13 DAS) compared to the control (10 DAS), reduced infection rate, increased germination rate, as well as higher agronomic performances (plant height, number of leaves) compared to the control at 7 – 49 DAS. Overall, this results indicated the potential of alginate seed-encapsulation techniques containing biocontrol agents to control plant diseases.